2021
DOI: 10.3390/app112411772
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Biochar in Pit Latrines as a Faecal Sludge Management Strategy to Reduce Water Resource Contaminations: A Review

Abstract: Faecal sludge management (FSM) in most developing countries is still insufficient. Sanitation challenges within the sub-Saharan region have led to recurring epidemics of water- and sanitation-related diseases. The use of pit latrines has been recognised as an option for on-site sanitation purposes. However, there is also concern that pit latrine leachates may cause harm to human and ecological health. Integrated approaches for improved access to water and sanitation through proper faecal sludge management are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The most common non-human waste deposited in latrines was ashes (77.1%), commonly added to minimize smell [57,58]. Ash has also been suggested to have the additional benefit of minimizing groundwater contamination from pit-latrines [59]. Smell is an important consideration within the non-human waste deposited in latrines as there are reports of "disinfectants, pesticides, oil, laundry and soapy water, detergents, and car-battery acids" being added to reduce smell from latrines [58].…”
Section: Discussionmentioning
confidence: 99%
“…The most common non-human waste deposited in latrines was ashes (77.1%), commonly added to minimize smell [57,58]. Ash has also been suggested to have the additional benefit of minimizing groundwater contamination from pit-latrines [59]. Smell is an important consideration within the non-human waste deposited in latrines as there are reports of "disinfectants, pesticides, oil, laundry and soapy water, detergents, and car-battery acids" being added to reduce smell from latrines [58].…”
Section: Discussionmentioning
confidence: 99%
“…Mamera et al [6] reviewed the literature published on the potential use of biochar, a carbon-rich adsorbent produced from different organic biomass, in faecal sludge management in developing countries. This work determined that biochar is a viable option for faecal sludge management due to its capacity to bind different inorganic and organic pollutants.…”
Section: Agricultural Residue Valorisation For Wastewater Treatmentmentioning
confidence: 99%
“…The use of biochar as a soil ameliorant has recently gained momentum in South Africa [ 4 ]. Numerous studies have shown the potential benefits of biochar in improving soil’s physical [ 5 , 6 ], chemical [ 7 , 8 ], and biological properties [ 5 , 9 ]. However, its application soon after the pyrolysis process, herein referred to as fresh biochar, has been reported to have detrimental effects.…”
Section: Introductionmentioning
confidence: 99%